An Asset-Based Analysis of Supply Chain Quality Management to the Collision of Information Technology - Arunkumar S (International Journal of Supply Chain Management, 2018)
The target of this paper expands upon earlier research, to give some new points of view in clarifying how Information Technology (IT) can make a maintained competitive advantage (MCA) and supply chain quality management (SCQM) capacities for the firm. The outcome demonstrates that the vast majority of IT assets are emphatically related with SCQM capacities and firm execution. Particularly, the outside-in and crossing assets will probably accomplish better supply chain quality capacities and give a MCA to firm execution.Keywords-Asset-Based analysis, Information Technology (IT), maintained competitive advantage (MCA), supply chain quality management (SCQM).Keywords-Asset-Based analysis, Information Technology (IT), maintained competitive advantage (MCA), supply chain quality management (SCQM).